Statistical Dashboards and Business Intelligence in Campus Information Systems: A Bibliometric Review of Implementation Trends - Ahmar, Ansari Saleh; Triutomo, Agung (PT Mattawang Mediatama Solution, 2025)
Campus academic information systems have become mission-critical infrastructure in higher education, yet a significant paradox persists. Many universities operate monolithic architectures that consolidate student data and administrative functions within unified platforms—offering inherent security advantages including centralized authentication, unified access control, and simplified vulnerability monitoring. However, scholarly discourse examining how these secure integrated systems can simultaneously achieve advanced business intelligence capabilities remains remarkably thin. This bibliometric study analyzes 749 publications from Scopus (2010-2025) to map the intellectual landscape of campus information systems research, with particular attention to security frameworks and statistical dashboard implementations. The methodology combines linear regression trend analysis (? = 2.54, p = 0.00135, R² = 0.5317), Bradford's Law, Lotka's Law, and k-means clustering (k = 9). Results reveal statistically significant publication growth (CAGR = 1.46%), accumulating 6,039 citations (mean = 8.06) across 1,945 authors from 86 countries. Indonesia dominates contributions (26.1%), followed by China (10.3%) and the United States (8.1%). Thematic analysis identifies nine research clusters, with security-focused studies employing PTES and OWASP methodologies achieving 83% intrusion detection accuracy, while governance evaluations using COBIT and ISO 27001 reveal system maturity gaps. Critically, fewer than 10% of publications address real-time analytics or decision support visualization within secure monolithic architectures. The collaboration index (3.03 authors/document) and degree of collaboration (83.2%) indicate robust interdisciplinary practices. Findings suggest that while security research has matured, significant gaps persist in integrating business intelligence dashboards with secure monolithic systems—highlighting urgent need for research bridging data protection frameworks with analytical capabilities.